Comparison of two warm-up models for obese and normal-weight adults performing supramaximal cycling exercise - Horia-Daniel, Iancu; Georges, Jabbour (Biology of Sport, 2018)
This study examines the impact of two forms of active warm-up on supramaximal cycling performance among sedentary adults. Thirty-seven adults [23.05 (6.4) years; BMI=26.05 (1.3) kg/m2, FM=30.1 (4.2)%, VO 2max =23.8 (5.8) ml/min/kg] participated in a cross-over randomized study, and all underwent a supramaximal cycling test (SCT) following 5 minutes of two models of warm-up pedalled at a constant velocity of 60 rpm. In the first experimental condition, the warm-up was set at 50% of maximal aerobic power (WU50%MAP). In the second experimental condition, the intensity was set at 50% of maximal heart rate (WU50%MHR). During both experimental conditions the rating of perceived exertion (RPE) at the end of the warm-up and the performance reduction in percentage (ΔPr%) during the SCT were recorded. During the WU50%MAP experimental condition, obese (OB) adults showed higher values of post-warm-up heart rate (~30%) than in the normal weight (NW) group (p<0.01). In addition, the RPE scores determined after the warm-up were significantly higher in OB compared to NW (~30%; p<0.01). However, after the WU50%MHR experimental condition, no significant differences remained between OB and NW. Moreover, the analyses showed a significant positive association between the elevated heart rate values observed after WU50%MAP and both RPE and ΔPr% (r= 0.71 and r =0.81, p <0.05 respectively). In contrast to NW individuals, the WU50%MHR seems to be more suitable for the OB group undergoing the SCT given that WU50%MAP affected supramaximal cycling performances.